Effects of World Crude Oil Prices on Crude Oil Import: Evidence from Pakistan (Journal of Asian Development Studies, 2015)
The objective of this paper is to analyze the long and short run effects of crude oil price on crude oil import demand of Pakistan by employing time series data from 1981-2014. The long run relationship between crude oil price and crude oil import was tested by using johansen and juselius cointegration approach. The short run effect is analyzed by using error correction model. The analyses reveal significant long run negative impact of prices on crude oil import demand of Pakistan. However this study found insignificant effect of respective variable in short run. Pakistan should take various energy efficiency and demand side management measures like expanding and strengthening indigenous resource base, imports of advance technology, substituting imported crude oil by domestic crude oil and looking for alternative energy sources.